2014
DOI: 10.1002/mus.24162
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial sonography in patients with myotonic dystrophy type 1

Abstract: TCS can offer new insight into structural changes of several cerebral areas in patients with DM1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
(58 reference statements)
2
25
1
Order By: Relevance
“…Previously, an association between RLS and sonographically detected abnormalities of the Substantia nigra in the sense of hypoechogenicity has been reported [10]. Congruently to the findings of Peric et al [16], we failed to confirm such an association in DMpatients. Also, in both TCS-studies the width of third ventricle was significantly larger in the patient group, most likely to be interpreted as an expression of the cerebral atrophy in myotonic dystrophies.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previously, an association between RLS and sonographically detected abnormalities of the Substantia nigra in the sense of hypoechogenicity has been reported [10]. Congruently to the findings of Peric et al [16], we failed to confirm such an association in DMpatients. Also, in both TCS-studies the width of third ventricle was significantly larger in the patient group, most likely to be interpreted as an expression of the cerebral atrophy in myotonic dystrophies.…”
Section: Discussionmentioning
confidence: 63%
“…TCS has become a reliable and sensitive diagnostic tool in the evaluation of extrapyramidal movement disorders, ataxias, and in many neurological disorders with psychiatric symptoms as well as in restless legs syndrome (RLS) [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. This is of particular interest since different features like depression, excessive daytime sleepiness (EDS) and RLS occur frequently in DM 1 and also in DM2 [11][12][13].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…MRI studies revealed a broad spectrum of abnormalitiers including white and grey matter abnormalities . So far, two studies evaluated TCS findings in patients with DM . Peric et al studied 66 patients with DM type 1 and detected reduced BR echogenicity in 25 (37.7%) of them .…”
Section: Tcs In Depressed Patients With Association To Neurodegeneratmentioning
confidence: 99%
“…TCS can depict abnormalities of the substantia nigra (SN) and basal ganglia that are less easily detected by other techniques . In addition, in patients with myotonic dystrophy type 1 (DM1), TCS has revealed an association between brainstem raphe (BR) hypoechogenicity and depression and fatigue, while diameter of the third ventricle (DTV) was enlarged, reflecting cerebral atrophy in the midline brain areas . Another TCS study revealed BR hypoechogenicity associated with EDS, SN hypoechogenicity, and increased DTV in both DM1 and DM2, but the number of patients in that study was small (17 DM1 and 14 DM2).…”
mentioning
confidence: 99%